Ayurveda management of Katigraha w.s.r to Lumbar Spondylosis - Shripathi , Acharya G; Acharya, Rajeshwari S (International Research Journal of Ayurveda & Yoga, 2021)
Degenerative joint disorders are on the rise in Indian population. As the age advances these bones get degenerated at the joint area and cause pain and disability in these patients. Osteoarthritis of the knee joint, OA of ankle joint, hip joint, and lumbar spine are the commonest forms degeneration. In lumbar spondylosis, the joint surfaces in lumbar spine develop degenerative changes and lead to Lumbar spondylosis. There will be decrease in joint space, degeneration in bones, and sclerotic changes in joint surfaces. There will also growth of osteophytes at the sides of vertebrae. There will be chronic low back ache and restriction of movement due to pain. X ray of lumbar spine, MRI and CT scans are contributory to the diagnosis of this disease. Ayurveda formulations are effective in the management of this disease. Ayurveda management of lumbar spondylosis include Vyadhi Pratyanika Aushadhi Prayoga, Panchakarma, Rasayana And Vedana Sthapaka Drugs, Pathyapathya Prayoga, diet therapy, and practice of yoga therapy. The present paper highlights the role of Ayurveda in the management of lumbar spondylosis.